Formal Semantics: Origins, Issues, Early Impact - Barbara H. Partee (The Baltic International Yearbook of Cognition, Logic and Communication, 2010)
Formal semantics and pragmatics as they have developed since the late 1960's have been shaped by fruitful interdisciplinary collaboration among linguists, philosophers, and logicians, among others, and in turn have had noticeable effects on developments in syntax, philosophy of language, computational linguistics, and cognitive science. In this paper I describe the environment in which formal semantics was born and took root, highlighting the differences in ways of thinking about natural language semantics in linguistics and in philosophy and logic. With Montague as a central but not solo player in the story, I reflect on crucial developments in the 1960's and 70's in linguistics and philosophy, and the growth of formal semantics and formal pragmatics from there. I discuss innovations, key players, and leading ideas that shaped the development of formal semantics and its relation to syntax, to pragmatics, and to the philosophy of language in its early years, and some central aspects of its early impact on those fields. References Abbott, B. 1999. ‘The formal approach to meaning: Formal semantics and its recent developments’. Journal of Foreign Languages (Shanghai)119, no. 1: 2–20. https://www.msu.edu/~abbottb/formal.htm. Ajdukiewicz, K. 1960. Je¸zyk i Poznanie (Language and Knowledge). Warsaw. Bach, E. 1968. ‘Nouns and Noun Phrases’. In E. Bach & R.T. Harms (eds.) ‘Universals in Linguistic Theory’, 90–122. NY: Holt, Rinehart & Winston. Bach, E. 1989. Informal Lectures on Formal Semantics. New York: State University of New York Press. Bar-Hillel, Y. 1954a. ‘Logical syntax and semantics’. Language 30: 230–237. http://dx.doi.org/10.2307/410265 Bar-Hillel, Y. 1954b. ‘Indexical Expressions’. Mind 63: 359–379. http://dx.doi.org/10.1093/mind/LXIII.251.359 Bar-Hillel, Y. 1963. ‘Remarks on Carnap’s Logical Syntax of Language’. In P. A. Schilpp (ed.) ‘The Philosophy of Rudolf Carnap’, 519–543. LaSalle, Illinois / London: Open Court / Cambridge University Press. Barker, C. & Jacobson, P. (eds.). 2007. Direct Compositionality. Oxford Studies in Theoretical Linguistics. Oxford: Oxford University Press. Bernstein, L. 1976. The unanswered question: six talks at Harvard: The Charles Eliot Norton Lectures 1973. Cambridge, Mass.: Harvard University Press. Bohnert, H. & Backer, P. 1967. ‘Automatic English-to-Logic Translation in a Simplified Model: A Study in the Logic of Grammar’. IBM Research Paper RC-1744. Yorktown Heights, NY: IBM. Burris, S. 2009. ‘The Algebra of Logic tradition’. In The Stanford Encyclopedia of Philosophy (Summer 2009 Edition), ed. Edward N. Zalta. Stanford: Stanford University. http://plato.stanford.edu/archives/sum2009/entries/algebra-logic-tradition/. Carnap, R. 1928. Der logische aufbau der welt. Berlin-Schlachtensee: Weltkreisverlag. Carnap, R. 1946. ‘Modalities and quantification’. The Journal of Symbolic Logic 11.2: 33–64. http://dx.doi.org/10.2307/2268610 Carnap, R. 1947. Meaning and Necessity: A Study in Semantics and Modal Logic. Chicago, Ill.: University of Chicago Press. Carnap, R. 1956. Meaning and Necessity: A Study in Semantics and Modal Logic. 2nd edition with supplements. Chicago: Phoenix Books, University of Chicago Press. Carnap, R. & Smeaton, A. 1937. The logical syntax of language: International library of psychology, philosophy and scientific method. London: Routledge & K. Paul Ltd. Chierchia, G. & McConnell-Ginet, S. 1990. Meaning and Grammar. An Introduction to Semantics. Cambridge: MIT Press. Chomsky, N. 1955. ‘Logical syntax and semantics: their linguistic relevance’. Language 31: 36–45. http://dx.doi.org/10.2307/410891 Chomsky, N. 1957. Syntactic Structures. The Hague: Mouton. Chomsky, N. 1965. Aspects of the Theory of Syntax. Cambridge, MA: MIT Press. Chomsky, N. 1971. ‘Deep structure, surface structure, and semantic interpretation’. In D. Steinberg & L. Jakobovits (eds.) ‘Semantics: An Interdisciplinary Reader in Philosophy, Linguistics, and Psychology’, 183–216. Cambridge: Cambridge University Press. Chomsky, N. 1975. ‘Questions of form and interpretation’. In R. Austerlitz (ed.) ‘The Scope of American Linguistics’, 159–196. Lisse: Peter de Ridder Press. Church, A. 1940. ‘A formulation of the simple theory of types’. Journal of Symbolic Logic 5: 56–68. http://dx.doi.org/10.2307/2266170 Church, A. 1951. ‘A formulation of the logic of sense and denotation’. In P. Henle, H. Kallen & S. Langer (eds.) ‘Structure, Method, and Meaning: Essays in Honor of H.M. Sheffer’, 3–24. New York: Liberal Arts Press. Cocchiarella, N. 1997. ‘Formally-oriented work in the philosophy of language’. In J.V. Canfield (ed.) ‘Philosophy of Meaning, Knowledge and Value in the 20th Century’, 39–75. London; New York: Routledge. Cresswell, M. J. 1978. ‘Semantic competence’. In F. Guenthner & M. Guenthner-Reutter (eds.) ‘Meaning and Translation: Philosophical and Linguistic Approaches’, 9–43. London: Duckworth. Davidson, D. 1964. ‘Theories of meaning and learnable languages’. In ‘Proceedings of the 1964 International Congress for Logic, Methodology, and Philosophy of Science’, Jerusalem: North-Holland. Davidson, D. 1967. ‘The logical form of action sentences’. In N. Rescher (ed.) ‘The Logic of Decision and Action’, 81–95. Pittsburgh: Pittsburgh University Press. Davidson, D. 1970. ‘Semantics for natural languages’. In B. Visentini (ed.) ‘Linguaggi nella Societa e nella Tecnica’, Milan: Edizioni di Comunita. Dowty, D. 1978a. A Guide to Montague’s PTQ. Bloomington, IN: Indiana University Linguistics Club. Dowty, D. 1978b. ‘Governed transformations as lexical rules in a Montague Grammar’. Linguistic Inquiry 9: 393–426. Dowty, D., Wall, R. E. & Peters, S. Jr. 1981. Introduction to Montague Semantics. Dordrecht: Reidel. Feferman, A. Burdman & Feferman, S. 2004. Alfred Tarski: Life and Logic. Cambridge: Cambridge University Press. Fodor, J. 1961. ‘Projection and paraphrase in semantics’. Analysis 21: 73–77. http://dx.doi.org/10.2307/3326914 Fodor, J. & Katz, J. (eds.). 1964. The Structure of Language: Readings in the Philosophy of Language. Englewood Cliffs: Prentice-Hall. Frege, G. 1892. ‘Über Sinn und Bedeutung’. Zeitschrift für Philosophie und philosophische Kritik: 22–50. English translation (On Sense and Nominatum) in P. Geach and M. Black (eds.) (1980) Translations from the Philosophical Writings of Gottlob Frege. Blackwell, Oxford. Reprinted in A. P. Martinich (ed.) (2000). Also reprinted in Ludlow (ed. 1997). Gamut, L. T. F. 1982. Logika, Taal en Betekenis. Vol 1: Inleiding in de logica. Vol 2: Intensionele logica en logische grammatica. De Meern, Netherlands: Het Spectrum. Gamut, L. T. F. 1991. Logic, Language, and Meaning. Vol. 1: Introduction to Logic. Vol. 2: Intensional Logic and Logical Grammar. Chicago: University of Chicago Press. Gazdar, G. 1982. ‘Phrase structure grammar’. In P. Jacobson & G. Pullum (eds.) ‘The Nature of Syntactic Representation’, 131–186. Dordrecht: D.Reidel. Gazdar, G., Klein, E., Pullum, G. & Sag, I. 1985. Generalized Phrase Structure Grammar. Oxford: Basil Blackwell. Geach, P. T. 1962. Reference and Generality. Ithaca: Cornell University Press. Geach, P. T. 1967. ‘Intentional identity’. Journal of Philosophy 64: 627–632. http://dx.doi.org/10.2307/2024459 Goodman, N. 1951. The Structure of Appearance. Cambridge, Mass.; Harvard University Press. Grice, P. 1892. ‘(originally 1967). Logic and conversation’. In Syntax and Semantics 3: Speech Acts, eds. Peter Cole and Jerry L. Morgan, 41–58. New York: Academic Press. Reprinted in Grice, Paul: 1989. Studies in the Way of Words. Cambridge, MA: Harvard University Press, pp 22–40. http://www.ucl.ac.uk/ls/studypacks/Grice-Logic.pdf. Harris, R. & Taylor, T. J. 1997. Landmarks in linguistic thought I, The Western tradition from Socrates to Saussure. 2nd edition. Routledge history of linguistic thought series. London: Routledge. Harris, R. A. 1993. The Linguistics Wars. New York and Oxford: Oxford University Press. Heim, I. 1982. The Semantics of Definite and Indefinite Noun Phrases. Ph.D. thesis, University of Massachusetts. Published 1989, New York: Garland. http://newstar.rinet.ru/~goga/biblio/heim (djvu) or http://semanticsarchive.net/Archive/Tk0ZmYyY/ (very large PDF file). Heim, I. & Kratzer, A. 1998. Semantics in Generative Grammar. Oxford: Blackwell. https://udrive.oit.umass.edu/partee/Semantics_Readings/Heim%26Kratzer.pdf. Hintikka, J. 1973. ‘Carnap’s heritage in logical semantics’. Synthese 25: 372–397. Hintikka, K. J. J. 1962. Knowledge and Belief. Ithaca, N.Y.: Cornell University Press. Hintikka, K. J. J., Moravcsik, J. & Suppes, P. (eds.). 1973. Approaches to Natural Language. Ithaca, N.Y.: Cornell University Press. Hodges, W. 1998. ‘Compositionality is not the problem’. Logic and Logical Philosophy 6:7–33. http://www.logika.umk.pl/llp/06/hodges.pdf. Hodges, W. 2001. ‘Formal Features of Compositionality’. Journal of Logic, Language and Information 10: 7–28. http://dx.doi.org/10.1023/A:1026502210492 Huck, G. J. & Goldsmith, J. A. 1995. Ideology and Linguistic Theory: Noam Chomsky and the Deep Structure Debates. London: Routledge. Jackendoff, R. 1972. Semantic Interpretation in Generative Grammar. Cambridge, Mass.: MIT Press. Jacobson, P. 1999. ‘Towards a variable-free semantics’. Linguistics and Philosophy 22: 117–184. http://dx.doi.org/10.1023/A:1005464228727 Janssen, T. M. V. 1983. Foundations and Applications of Montague Grammar. Amsterdam: Mathematisch Centrum, University of Amsterdam. Kalish, D. & Montague, R. 1964. Logic: Techniques of Formal Reasoning. New York: Harcourt, Brace & World, Inc. Kalish, D., Montague, R., Mar, G. & Fogelin, R. J. 1980. Logic : Techniques of Formal Reasoning. New York: Harcourt Brace Jovanovich. Kanger, S. 1957a. ‘The Morning Star Paradox’. Theoria 23: 1–11. http://dx.doi.org/10.1111/j.1755-2567.1957.tb00263.x Kanger, S. 1957b. ‘A note on quantification and modalities’. Theoria 23: 133–134. Kaplan, D. 1964. Foundations of Intensional Logic. Ph.D. thesis, University of California Los Angeles. Karttunen, L. 1968. What do Referential Indices Refer to? Santa Monica, CA: The Rand Corporation. Karttunen, L. 1969. ‘Pronouns and Variables’. In ‘CLS 5’, 108–116. Chicago: Chicago Linguistic Society, University of Chicago. Katz, J. J. 1961. ‘A reply to “Projection and paraphrase in semantics”’. Analysis 22: 36–41. http://dx.doi.org/10.2307/3326856 Katz, J. J. 1981. Language and Other Abstract Objects. Totowa, New Jersey: Rowan & Littlefield. Katz, J. J. & Fodor, J. 1962. ‘What’s wrong with the philosophy of language?’ Inquiry 5: 197–237. http://dx.doi.org/10.1080/00201746208601351 Katz, J. J. & Fodor, J. 1963. ‘The structure of a semantic theory’. Language 39: 170–210. Reprinted in J. Fodor and J. Katz (eds.) (1964) The Structure of Language: Readings in the Philosophy of Language, 479-518. Katz, J. J. & Katz, F. 1977. ‘Is necessity the mother of intention?’ Philosophical Review 86: 70–96. http://dx.doi.org/10.2307/2184163 Katz, J. J. & Postal, P. M. 1964. An Integrated Theory of Linguistic Descriptions. Cambridge, MA: MIT Press. Keenan, E. (ed.). 1975. Formal Semantics of Natural Language. Cambridge: Cambridge University Press. King, J. C. 2011. ‘Structured propositions’. In The Stanford Encyclopedia of Philosophy (Fall 2011 Edition), ed. Edward N. Zalta. Stanford: Stanford University. http://plato.stanford.edu/archives/fall2011/entries/propositions-structured/. Kratzer, A. 1977. ‘What Must and Can Must and Can Mean’. Linguistics and Philosophy 1: 337–355. http://dx.doi.org/10.1007/BF00353453 Kripke, S. 1959. ‘A Completeness Theorem in Modal Logic’. Journal of Symbolic Logic 24: 1–14. http://dx.doi.org/10.2307/2964568 Kripke, S. 1963. ‘Semantical considerations on modal logic’. Acta Philosophica Fennica 16: 83–94. Kripke, S. 1972. ‘Naming and necessity’. In Semantics of Natural Language, eds. D. Davidson and G.F. Harman, 253–355 and addendum 763–769. Dordrecht: Reidel. Lakoff, G. 1968. Pronouns and Reference. Parts I and II. Bloomington: Indiana University Linguistics Club. Lewis, D. 1970. ‘General semantics’. Synthese 22: 18–67. Reprinted in Davidson and Harman, eds. Semantics of Natural Language, 1972, Dordrecht: Reidel. 169–218. Also reprinted in Partee 1976, 1–50. Link, G. 1979. Montague-Grammatik. Die logische Grundlagen. Munich: Wilhelm Fink Verlag. May, R. 1977. The grammar of quantification. Ph.D. thesis, MIT. McCawley, J. 1968. ‘The Role of Semantics in a Grammar’. In E. Bach & R. Harms (eds.)‘Universals in Linguistic Theory’, 124–169. New York: Holt, Rinehart, & Winston. McCawley, J. 1971. ‘Where do Noun Phrases come from?’ In D. Steinberg & L. Jakobovits (eds.)‘Semantics. An Interdisciplinary Reader in Philosophy, Linguistics and Psychology’, 217–231. Cambridge: Cambridge University Press. Montague, R. 1960. ‘Logical necessity, physical necessity, ethics, and quantifiers’. Inquiry 4: 259–269. Reprinted in Montague (1974), 71–83. Montague, R. 1968. ‘Pragmatics’. In R. Klibanski (ed.) ‘Contemporary Philosophy’, 102–121. Florence: La Nuova Italia Editrice. Reprinted in Montague (1974), 95–118. Montague, R. 1969. ‘On the Nature of Certain Philosophical Entities’. The Monist 53: 159–194. Reprinted in Montague (1974), 148–187. Montague, R. 1970a. ‘Pragmatics and intensional logic’. Synthese 22: 68–94. Reprinted in Davidson and Harman, eds., 1972, 142-168; Reprinted in Montague (1974), 119–147. Montague, R. 1970b. ‘Universal grammar’. Theoria 36: 373–398. Reprinted in Montague (1974),222–246. Montague, R. 1970c. ‘English as a Formal Language’. In B. Visentini (ed.) ‘Linguaggi nella Societá e nella Tecnica’, 189–224. Milan: Edizioni di Comunità. Reprinted in Montague (1974), 188–221. Montague, R. 1973. ‘The proper treatment of quantification in ordinary English’. In J. M. E. Moravcsik K. J. J. Hintikka & P. Suppes (eds.) ‘Approaches to Natural Language’, 221–242. Dordrecht: Reidel. Reprinted in Montague (1974), 247–270; Reprinted in Portner and Partee, eds., 2002, 17–34 http://newstar.rinet.ru/~goga/biblio/essential-readings/01-Montague-The.Proper.Treatment.of.Quantification.in.Ordinar Montague, R. 1974. Formal Philosophy. Selected Papers of Richard Montague. New Haven/London: Yale University Press. Edited and with an introduction by Richmond H. Thomason. Newmeyer, F. J. 1980. Linguistic Theory in America: The First Quarter Century of Transformational Generative Grammar. New York: Academic Press. Parsons, T. 1968. ‘A semantics for English’. Ms. Parsons, T. 1972. ‘An Outline of a Semantics of English’. Ms. University of Massachusetts, Amherst. Partee, B. H. 1971. ‘On the requirement that transformations preserve meaning’. In C. J. Fillmore & D. T. Langendoen (eds.) ‘Studies in Linguistic Semantics’, 1–21. Holt, Rinehart, and Winston. Partee, B. H. 1973a. ‘The semantics of belief-sentences’. In J. M. E. Moravcsik K. J. J. Hintikka & P. Suppes (eds.) ‘Approaches to Natural Language’, 309–336. Dordrecht: Reidel. Partee, B. H. 1973b. ‘Some transformational extensions of Montague grammar’. Journal of Philosophical Logic 2: 509–534. Reprinted in Partee (1976), pp. 51–76. http://semanticsarchive.net/Archive/TEwODQ3Z/. Partee, B. H. 1973c. ‘Comments on Montague’s paper’. In J. M. E. Moravcsik K. J. J. Hintikka & P. Suppes (eds.) ‘Approaches to Natural Language’, 243–258. Dordrecht: Reidel. Partee, B. H. 1975. ‘Montague grammar and transformational grammar’. Linguistic Inquiry 6: 203–300. Partee, B. H. (ed.). 1976. Montague Grammar. New York: Academic Press. Partee, B. H. 1979. ‘Semantics - mathematics or psychology?’ In R. Bäuerle, U. Egli & A. von Stechow (eds.) ‘Semantics from Different Points of View’, 1–14. Berlin: Springer-Verlag. Partee, B. H. 1982. ‘Belief-sentences and the limits of semantics’. In S. Peters & E. Saarinen (eds.) ‘Processes, beliefs, and questions’, 87–106. Dordrecht: Reidel. Partee, B. H. 1988. ‘Possible worlds in model-theoretic semantics: a linguistic perspective’. In S. Allén (ed.) ‘Possible Worlds in Humanities, Arts, and Sciences. Proceedings of Nobel Symposium 65’, 93–123. Berlin & New York: Walter de Gruyter. http://semanticsarchive.net/Archive/TA4MTYxZ/. Partee, B. H. 1996. ‘The development of formal semantics in linguistic theory’. In S. Lappin (ed.) ‘The Handbook of Contemporary Semantic Theory’, 11–38. Oxford: Blackwell. http://bhpartee.narod.ru/Partee_1996DevelofFormalSemantics.pdf. Partee, B. H. 2004. ‘Reflections of a formal semanticist’. In S. Lappin (ed.) ‘Compositionality in Formal Semantics: Selected Papers by Barbara H. Partee’, 1–25. Oxford: Blackwell Publishing. Partee, B. H. 2005. ‘Reflections of a formal semanticist as of Feb 2005’. http://people.umass.edu/partee/docs/BHP_Essay_Feb05.pdf. Partee, B. H. 2009. ‘Perspectives on Semantics: How philosophy and syntax have shaped the development of formal semantics, and vice versa’. In Conference “Russian in Contrast”, Special guest lecture. University of Oslo, Oslo. Video and Poster: http://folk.uio.no/atleg/russian_in_contrast/; Power Point presentation: https://udrive.oit.umass.edu/partee/Partee2009Oslo.ppt.pdf. Partee, B. H. & Hendriks, H. L. W. 1997. ‘Montague grammar’. In J. van Benthem & A. ter Meulen (eds.) ‘Handbook of Logic and Language’, 5–91. Amsterdam / Cambridge, MA: Elsevier / MIT Press. https://udrive.oit.umass.edu/partee/LOLA01Partee.PDF. Partee, B. H., ter Meulen, A. & Wall, R. (eds.). 1990. Mathematical Methods in Linguistics. Dordrecht: Kluwer. Pelletier, F. J. 1982. ‘X’. Notre Dame Journal of Formal Logic 23: 316–326. http://dx.doi.org/10.1305/ndjfl/1093870091 Pelletier, F. J. 2001. ‘Did Frege believe Frege’s principle?’ Journal of Logic, Language and Information 10: 87–114. http://dx.doi.org/10.1023/A:1026594023292 Peters, P. S. & Ritchie, R. W. 1973. ‘On the generative power of transformational grammars’. Information Sciences 6: 49–83. http://dx.doi.org/10.1016/0020-0255(73)90027-3 Prior, A. 1967. Past, Present, and Future. Oxford: Oxford University Press. Quine, W. V. 1960. Word and Object. Cambridge, Mass.: MIT Press. Quine, W. V. 1970. Philosophy of Logic. Englewoon Cliffs, N.J.: Prentice-Hall. Quine, W. V. 1986. ‘Autobiography of W.V. Quine’. In Lewis Edwin Hahn & Paul Arthur Schilpp (eds.) ‘The Philosophy of W.V. Quine’, 3–48. La Salle, IL: Open Court. Reichenbach, H. 1947. Elements of Symbolic Logic. New York, London: MacMillan. Reinhart, T. 1976. The Syntactic Domain of Anaphora. Ph.D. thesis, MIT. Reinhart, T. 1983. ‘Coreference and bound anaphora: A restatement of the anaphora question’. Linguistics and Philosophy 6: 47–88. http://dx.doi.org/10.1007/BF00868090 Russell, B. 1957. ‘Mr. Strawson on Referring’. Mind 66: 385–389. http://dx.doi.org/10.1093/mind/LXVI.263.385 Scott, D. 1970. ‘Advice on modal logic’. In K. Lambert (ed.) ‘Philosophical Problems in Logic. Some Recent Developments’, 143–174. Dordrecht: Reidel. Seuren, P. 1998. Western Linguistics: An Historical Introduction. Wiley-Blackwell. Soames, S. 1985. ‘Lost innocence’. Linguistics and Philosophy 8: 59–72. http://dx.doi.org/10.1007/BF00653375 Soames, S. 2010. Philosophy of Language. Princeton: Princeton University Press. Stalnaker, R. 1984. Inquiry. Cambridge, Mass.: MIT Press. Soames, S. 1999. Context and Content. Oxford: Oxford University Press. Stanley, J. 2008. ‘Philosophy of Language in the Twentieth Century’. In D. Moran (ed.) ‘The Routledge Companion to Twentieth Century Philosophy’, 382–437. London: Routledge Press. Stokhof, M. 2006. ‘The development of Montague grammar’. In S. Auroux, E.F.K. Koerner, H-J. Niederehe & K. Versteegh (eds.) ‘History of the Language Sciences’, 2058–2073. Berlin – New York: Walter de Gruyter. Strawson, P. F. 1950. ‘On Referring’. Mind 59: 320–344. http://dx.doi.org/10.1093/mind/LIX.235.320 Tarski, A. 1935. ‘Der Wahrheitsbegriff in den formalisierten Sprachen’. Studia Philosophica 1: 261–405. Reprinted in Tarski (1986), Collected Papers, Vol. 2, Birkhäuser, Basel. Thomason, R. 1976. ‘Some extensions of Montague grammar’. In B. H. Partee (ed.) ‘Montague Grammar’, 77–118. New York: Academic Press. Vermazen, B. 1967. ‘Review of J.J. Katz and P.Postal (1964), “An Integrated Theory of Linguistic Descriptions”, and J.J.Katz (1966), “The Philosophy of Language”’. Synthese 17: 350–365.